(untitled) (Journal of Scientific Research, 2025)
The present investigation aimed to enhance the identification of polycyclic aromatic hydrocarbons in water and beverages by employing large-volume injection (LVI) in conjunction with membrane-assisted solvent extraction for gas chromatography-mass spectrometry analyses. High-purity solvents and isotope-labeled standards were used to calibrate and create polycyclic aromatic hydrocarbon (PAH) standards. Water samples from polluted rivers in India and commercially available beverages were collected and preserved under controlled conditions. Microwave-assisted solvent extraction (MASE) was optimized by adjusting temperature and pH for efficient extraction. The extracts were analyzed using gas chromatography-mass spectrometry (GC-MS) with a large-volume injection system for sensitive PAH detection. MASE-LVI-GC-MS efficiently determined 16 PAHs in aqueous samples by optimizing extraction parameters like shaking speed, temperature, and solvent composition. Recovery percentages were above 65 %, and a relative standard deviation of 6 % guaranteed repeatability to 18 % during five consecutive extractions. It was shown that great sensitivity was achieved by reaching detection limits within the range of nanograms per litre. In conclusion, membrane-assisted solvent extraction combined with large-volume injection and GC-MS efficiently detects PAHs in various water and beverage samples, achieving nanogram-per-liter sensitivity. It offers uniform extraction, rapid analysis, and reduced solvent use across diverse matrices.